2005
DOI: 10.1103/physrevb.71.035413
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption on hydroxylated silica surfaces studied using the density functional theory

Abstract: We present an ab initio investigation of water adsorption on ordered hydroxylated silica surfaces, using the density functional theory within the ultrasoft pseudopotentials and generalized-gradient approximation. The ͑100͒ and ͑111͒ surfaces of the hydroxylated cristobalite are used as substrates to adsorb water clusters and overlayers. Water adsorbs through hydrogen bonds formed between water and surface hydroxyl groups on the ␤͑␣͒-cristobalite ͑100͒ surface. A large enhancement of the hydrogen bonding in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 57 publications
10
104
0
2
Order By: Relevance
“…340 In contrast, on the C(111) surface which exhibits non-interacting silanols (separated by 5Å), water adsorbs in a hollow site and is double proton-donor and a protonacceptor. 573 This example shows the limits of cluster models to mimick non-interacting silanols. Ref.…”
Section: The Low Coverage Casementioning
confidence: 99%
See 3 more Smart Citations
“…340 In contrast, on the C(111) surface which exhibits non-interacting silanols (separated by 5Å), water adsorbs in a hollow site and is double proton-donor and a protonacceptor. 573 This example shows the limits of cluster models to mimick non-interacting silanols. Ref.…”
Section: The Low Coverage Casementioning
confidence: 99%
“…An even more complex pattern occurs on the C(100) surface with water bridging the geminal silanol pairs and accepting an additional H-bond from a silanol ( Figure 41d). 573 The complexity of these surface structures cannot be easily modeled by a cluster approach.…”
Section: The Low Coverage Casementioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested that in the case of the first water layer formation, the water molecules were in a more localized state thus the calculated value of isosteric heat and the differential entropy was higher than for second and third layer. More recent works [35,36], extended on high silica zeolites and mesoporous silicas (BEA, SBA-15, MCM-41), maintained earlier conclusions demonstrating that the measured heat of adsorption of water (100 \ q diff \ 44 kJ mol -1 ), directly related to the bond energies between water and sorption centres, was larger than the heat of liquefaction of water (44 kJ mol -1 ) in the whole coverage. The type of silanol groups, being the sorption centres, as well as the geometry of water adsorptive adduct, was also considered as factors affecting the sorption process and measured heats of adsorption.…”
Section: Resultsmentioning
confidence: 78%